2018
DOI: 10.13031/trans.12826
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of the Modern Pig

Abstract: Abstract. It is important to know the physical dimensions of livestock to properly design confined animal housing facilities as well as feeding and drinking equipment. An engineering standard for the dimensions of livestock and poultry published by ASABE reports swine dimensions that were originally published in 1968. Changes in animal husbandry practices for swine, such as improved and new genetic lines, nutrition and feed form, and improved facility and equipment design, make it necessary to validate or upda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 0 publications
5
16
0
Order By: Relevance
“…The overall shape and relationship of the dimension curves (L, H, W) are similar to those in older literature and recent studies (Figure 2; Table 1; Midwest Plan Service, 1983;ASABE, 2011;Condotta et al, 2018). Notably, this set of dimension data shows that at birth, piglets are smaller in all dimensions.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The overall shape and relationship of the dimension curves (L, H, W) are similar to those in older literature and recent studies (Figure 2; Table 1; Midwest Plan Service, 1983;ASABE, 2011;Condotta et al, 2018). Notably, this set of dimension data shows that at birth, piglets are smaller in all dimensions.…”
Section: Discussionsupporting
confidence: 86%
“…; Digital Outside Calipers, Igaging, San Clemente, CA, USA), and BW was measured using a hanging bucket scale (±0.10 kg, 300 kg capacity; W1478, Performance Tools, Tukwila, WA, USA). Depth (i.e., abdomen to top of spine) measurement was not measured as recent research has shown that this measurement does not differ from the width of the piglet at and below 20 kg based on the 95% confidence interval (Condotta et al, 2018).…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The images were processed and analyzed using methods proposed by Condotta et al (2018a) and Condotta et al (2018b) to acquire the pig's projected volume (px cm) ( Fig. 6).…”
Section: Field Test Of Cameras 251 Animal Phenotypic Data Evaluationmentioning
confidence: 99%